NILAI BUDAYA DAN KEBERSAMAAN DALAM PERMAINAN RANGKU ALU SEBAGAI SUMBER BELAJAR KONTEKSTUAL BAGI SISWA SEKOLAH DASAR - Nadia vega; Siti Ni'matul Fitriyah; Muhammad Fauzy Emqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on contextual learning theory, which emphasizes the connection between learning materials and students’ real-life experiences, as well as cultural values theory that plays an important role in shaping students’ character and behavior. The problem in this study is the low understanding of cultural values and the lack of active student participation in the learning process. Therefore, it is necessary to implement meaningful and contextual learning innovations through the use of traditional games. This study aims to identify the cultural values and togetherness contained in the traditional game Rangku Alu and its utilization as a contextual learning resource for fourth-grade students at SDN Merjosari 1 Malang City.This research used a qualitative method with a case study approach. The subjects of this study were the school principal, the fourth-grade teacher, and fourth-grade students. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results show that the Rangku Alu game contains cultural values such as cooperation, discipline, responsibility, and mutual respect. In addition, the use of Rangku Alu in learning can increase students’ activeness, participation, and motivation because the learning process is related to real-life experiences and local culture. The integration of traditional games also creates a more enjoyable and meaningful learning environment.In conclusion, the use of the Rangku Alu traditional game as a contextual learning resource has a positive impact on instilling cultural values and togetherness, as well as improving the quality of learning in elementary schools.